Я познаю мир : коллекции и коллекционеры: дет. энцикл. / сост. С. Истомин ; худож. А. Аешин - Истомин С. (АСТ, 1999)
Экземпляры: (20170119) / Инвентарный номер: / Цена: / Сис.шифр: 79.18 / Авт.знак: Я 11 / ББК: 79.18я92